ANALISIS EFEKTIVITAS PENERAPAN SISTEM DIGITALISASI ASET DAERAH MENGGUNAKAN SOFTWARE APLIKASI SIMASDA (STUDI KASUS PADA BKAD PEMERINTAH KOTA BOGOR) - Fadhilah, Rangga Muhamad; Surya, Rendra Trisyanto (Indonesian Accounting Research Journal, 2024)
In realizing the vision of the Bogor City Government BKAD, which is realizing accountable and professional regional financial and asset management, the Bogor City Government created an application called SIMASDA (Regional Asset Management System). With the SIMASDA application, asset administration at BKAD can be more structured in terms of input and output it produces. This application can also help inventory assets, so that assets can be presented and informed accurately and quickly. In addition, the entire community can view the application directly through a special website with the barcode scan method which will later display data from the asset (because it is internet/online based). In measuring effectiveness in this research using the PIECES theory put forward by Ragil Wukir. Based on the results of the analysis adapted to the PIECES theory, it can be seen that the effectiveness of the SIMASDA application is good and feasible to use in terms of the features in the SIMASDA application which are adjusted to the indicators of performance, information, economy, control, efficiency and service. However, there are still problems with inputting regional asset documents into the SIMASDA application which have not been resolved to date. From these results it can be concluded that the SIMASDA application has been appropriate and well used by the BKAD Bogor City Government in terms of the features in the SIMASDA application, but in terms of inputting regional asset document data entry it has not been resolved due to the lack of firmness in controlling regional asset documents that are still has not been inputted into the SIMASDA application, the human resources are still less sensitive to the management of scattered asset documents.